Dialogue summary: Planning now for the future of technology-enabled healthcare work in Ontario - Moat, KA; Lavis, JN (My University, 2023)
A thematic summary of what was learned from the stakeholder dialogue on planning now for the future of technology-enabled healthcare work in Ontario, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: planning; future; technology-enabled; healthcare; Ontario; work